Strengthening The Pancasila Student Profile Through Guided Inquiry-Based Worksheets on Heat - Muhammad Farhan; Saiyidah Mahtari; Suyidno Suyidno (Jurnal Ilmiah Pendidikan Fisika, 2026)
The character of the Pancasila Student Profile in schools remains a challenge, especially in its integration into the science learning process. The study aims to develop a student worksheet based on a guided inquiry model using heated material to train the character of independence, cooperation, and critical reasoning. The development was carried out using the 4D model and tested using a one-group pretest-posttest design. Two experts and one practitioner assessed the product's validity, while field trials were conducted with high school students/equivalents. Practicality was measured through the implementation of learning and student responses, while effectiveness was assessed by reviewing character strengthening and improvements in learning outcomes using N-gain analysis. Thus, the student worksheet was classified as valid with the validation results of the student worksheet (3.35), outcome test (3.32), and the Pancasila student profile questionnaire (3.40) in the valid category; practical with the value of the implementation of learning (3.27) and student responses (3.24) in the practical category; and effective with an N-gain value of 0.77 for learning outcomes and a Pancasila character achievement of 3.10 in the good category. Thus, the developed student worksheet has proven to be feasible, practical, and effective in training students to embody the Pancasila student profile and improving student learning outcomes. The findings imply that guided inquiry-based student worksheets are effective in enhancing students’ critical reasoning, independence, and cooperation, with the most significant improvement observed in critical reasoning, as well as substantially improving learning outcomes. Therefore, teachers are recommended to design and implement structured inquiry-based worksheets, particularly in abstract topics such as heat, to simultaneously support students’ cognitive development and the strengthening of the Pancasila student profile's character.